2020
DOI: 10.1103/physrevb.101.180301
|View full text |Cite
|
Sign up to set email alerts
|

Growth of mutual information in a quenched one-dimensional open quantum many-body system

Abstract: We study the temporal evolution of the mutual information (MI) in a one-dimensional transverse Ising chain, coupled to a local fermionic Markovian bath, subsequent to a global quench of the transverse field. In the unitary case, the MI (or equivalently the bipartite entanglement entropy) saturates to a steady state value (obeying a volume law) following a ballistic growth. On the contrary, we establish that in the dissipative case the MI is exponentially damped both during the initial ballistic growth as well … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 67 publications
1
34
0
Order By: Relevance
“…Figure 4 illustrates the time evolution of R 3 for (a) connected and (b) disconnected subsystems AB, respectively. The appearing peaks of R 3 have been predicted and analyzed for various one-dimensional quantum systems subject to local interactions [61,62] (and have also been studied in the context of Rényi mutual information [72,73]). They can be understood in terms of propagating quasi-particles which [10].…”
Section: ½1mentioning
confidence: 99%
“…Figure 4 illustrates the time evolution of R 3 for (a) connected and (b) disconnected subsystems AB, respectively. The appearing peaks of R 3 have been predicted and analyzed for various one-dimensional quantum systems subject to local interactions [61,62] (and have also been studied in the context of Rényi mutual information [72,73]). They can be understood in terms of propagating quasi-particles which [10].…”
Section: ½1mentioning
confidence: 99%
“…The linear spreading of entanglement entropy turns out to be very general and holds in various noninteracting [19][20][21][22][23][24][25] and short-range interacting [26][27][28][29][30] models, also for inhomogeneous initial states [32,33]. (However, deviations from the linear growth can be found in a presence of Markovian bath [49].) The linear growth of entanglement is due to the maximal speed of information.…”
Section: A Entanglement Entropymentioning
confidence: 96%
“…In this respect, a main step forward has been taken in Ref. [235] (see also [236]), where it was shown that the quasiparticle picture can be adapted to the dynamic of some open quantum systems. In these systems, the spreading of entanglement is still governed by quasiparticles, but the environment introduces incoherent effects on top of it.…”
Section: Open Systemsmentioning
confidence: 99%